Women's Underrepresentation in Iraqi Parliamentary Committees: A Constitutional Analysis of Equality and Parliamentary Representation - Esraa Alsamee (Sriwijaya Law Review, 2026)
Despite the constitutional guarantees of equality and women’s political participation under the Iraqi Constitution, women remain underrepresented in parliamentary committees, particularly in influential committees responsible for legislative oversight and policymaking. This article examines whether the legal framework governing committee formation effectively implements the constitutional principles of equality and representative democracy. The study adopts a doctrinal legal methodology, supported by comparative legal analysis, examining the Iraqi Constitution, the Rules of Procedure of the Council of Representatives, relevant national legislation, and applicable international legal instruments, particularly the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). The analysis indicates that constitutional guarantees of parliamentary representation have not consistently translated into substantive participation in parliamentary committees. The findings suggest that existing committee allocation procedures, together with political party practices and the absence of binding legal criteria, restrict women's access to influential committees and may weaken the effective realisation of constitutional equality. The article argues that electoral quotas alone are insufficient to ensure substantive constitutional equality. It concludes that strengthening the legal framework governing committee membership, together with transparent allocation procedures and institutional safeguards, would better support women's effective participation in parliamentary decision-making.